Assessing the predictive power of psychological empowerment and health literacy for older patients' participation in health care: a cross-sectional population-based study. Issue 1 (December 2017) - Sak, Gabriele; Rothenfluh, Fabia; Schulz, Peter
Abstract Background Research has confirmed a positive link between patient involvement in decision-making and improvements in health outcomes. The objective of this study was to examine the roles of psychological empowerment and health literacy on the elderly's willingness to engage in treatment decisions. Methods A self-administered questionnaire was completed by a randomly selected sample of Swiss adults aged 65–80 years old (N = 826). Multivariate logistic regression was applied to determine the contribution of health literacy, psychological empowerment, and trust in physician on participants' preference to be active, collaborative or passive in decision-making. Results Most of the survey respondents preferred some participation in dealing with health related decisions (collaborative: 51%, and active: 35.6%). More than two-thirds of the sample was satisfied with their current involvement in medical decision-making (72.7%). Roughly one-fifth (18.8%) wished to attain a more active engagement than currently experienced, and the remainder of the sample preferred the opposite (8.5%). Due to higher reported levels of psychological empowerment and health literacy, Swiss-German seniors significantly preferred and assumed higher participation in medical decisions than Swiss-Italians. Psychological empowerment correlated with older adults' preferred and perceived involvement in medical decision-making. However, health literacy only predicted actual involvement in the last treatment decision that had to be made, differentiating only the active from the passive involvement group. Additionally, this research showed that health literacy mediated the relationship between psychological empowerment and the actual involvement in the last treatment decision that had to be made by the participant. Trust in physician and age appeared to be barriers to involvement, whereas education served as a facilitator. Conclusions As older adults' health literacy plays a role in individuals' willingness to attain an active role in health care decision-making, public health efforts should aim at developing programs and appropriate information that facilitate this process, especially for individuals with moderate or lower levels of health literacy. The current investigation showed that adequate health literacy levels are essential (but not sufficient) in order to reach higher rates of participation in the healthcare context. This research complements past evidence by adding knowledge on the psychosocial antecedents, and their combined effects on patients' involvement in healthcare.